Nutrition and exercise as a way for controlling aging - Pařizková, Jana (Array, 1990)
Nutrition and exercise are two factors which can be controlled and which may play an important role in determining life expectancy. Both nutritional requirements and exercise capacity change with increasing age and any programme designed to promote healthy aging should take such changes into account. Animal experiments have shown that spontaneously-active animals subsisting on limited diets have life-expectancy superior to inactive and well-fed controls. Dietary patterns in much of the world and especially in some of the eastern European countries have become unhealthy in the amount of fat meat and sugar consumed. In countries where this pattern is most pronounced, high mortality rates for cardiovascular diseases and neoplastic disease are evident.